Dramatic improvement in the mechanical properties of polydopamine/polyacrylamide hydrogel mediated human amniotic membrane. Issue 6 (25th January 2023) - Peng, Lin; Liang, Yufei; Yue, Jianling; Li, Hanmei; Deng, Aimin; Xie, Shun; Tang, Xiu-Zhi; Wang, Jing; Mao, Zenghui
Abstract : Dramatically improved mechanical properties of human amniotic membrane modified by PDA/PAM hydrogel due to the strong interface bonding. Abstract : Human amniotic membrane (hAM) is a promising material for tissue engineering due to several benefits, including desirable biocompatibility, stem cell source, antibacterial activity, etc . However, because of its low elasticity, the clinical application of hAM is severely restricted. To solve this issue, we employed polydopamine/polyacrylamide (PDA/PAM) hydrogels to toughen hAM. The test results indicated that the PDA/PAM hydrogel can enhance the toughness of hAM dramatically due to the formation of abundant chemical bonds and the strong mechanical properties of the hydrogel itself. Compared to pure hAM, the break elongation and tensile strength of PDA/PAM-toughened hAM rose by 154.15 and 492.31%, respectively. And most importantly, the fracture toughness was almost 15 times higher than untreated hAM. In addition, the cytotoxicity of the PDA/PAM-coated hAM was not detected due to the superior biocompatibility of the chemicals used in the study. Treating hAM with adhesive hydrogels to increase its mechanical characteristics will further promote the application of hAM as a tissue engineering material.